EDUCATIONAL TRANSFORMATION IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0: CHALLENGES AND INTEGRATION OF LOCAL WISDOM - Gamal Abdul Natsir; Samsudin; Junaidin (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
The Industrial Revolution 4.0 has brought significant transformations in the world of education, including changes in learning methods, evaluation systems, and educational policies. This study aims to analyze the challenges and opportunities of education in the era of the Industrial Revolution 4.0 and to examine its implications based on the theories of constructivism, humanism, and connectivism. This research employs a descriptive-analytical approach through a literature review of various recent studies related to the integration of technology and local wisdom in education. The results indicate that educational transformation in the digital era requires teachers to possess adaptive technological and pedagogical competencies. Meanwhile, the curriculum must be oriented toward strengthening digital literacy, critical thinking, and project-based learning. The integration of local wisdom emerges as an important strategy to preserve cultural identity amid the rapid flow of technological globalization. From the perspective of learning theories, the application of technology in education aligns with constructivist principles that emphasize active and collaborative learning, humanistic theory which focuses on the holistic development of individuals, and connectivist theory that highlights the importance of digital networks as new learning spaces. The implications of this study underscore the need for progressive educational policies, the strengthening of educators’ digital competencies, and the design of adaptive curricula that integrate human values, local culture, and technological innovation. These efforts are essential to realize an inclusive, character-based education system that enhances global competitiveness.